Cytotoxicity of Zirconomer and Conventional Glass Ionomer for L929 Murine Fibroblasts Over Time : Cytotoxicity of Zirconomer and Glass Ionomer - Ghahremani Ahsan , Mitra; Emamieh , Shila; Torabzadeh , Hasan; Yadegari, Dr. Zahra (Journal of Dental School, 2022)
Objectives This study sought to assess the cytotoxicity of zirconomer and conventional glass ionomer (CGI) for L929 murine fibroblasts over time. Methods In this in vitro, experimental study, 48 discs were fabricated from FX-II CGI and Shofu zirconomer and divided into three groups (n=16) for assessment of extracts obtained after 15 minutes (group 1), 24 hours (group 2) and seven days (group 3) of incubation following their initial polymerization. L929 murine fibroblasts were cultured and after 24 hours, they were exposed to extracts of the 48 discs in 144 wells. Cell-culture plates were incubated for 24, 48 and 72 hours. Cytotoxicity was evaluated using the methyl thiazolyl tetrazolium (MTT) assay. Data were analyzed by one-way and two-way ANOVA, Tukey’s test and independent sample t-test (P<0.05). Results At 24 hours, the 15-minute extract of both materials showed the highest cytotoxicity while the 7-day extract of the materials showed the lowest cytotoxicity. The 15-minute extract of zirconomer showed significantly higher cytotoxicity than CGI (P<0.05). At 48 hours, the cytotoxicity of 15-minute, 24-hour and 7-day extracts of zirconomer decreased. The results for CGI at 48 hours were similar to those at 24 hours. The 15-minute extract of zirconomer had significantly higher cytotoxicity than that of CGI (P<0.05). At 72 hours, the results in both groups were the same as those at 24 hours, and all zirconomer extracts showed significantly higher cytotoxicity than CGI extracts. Conclusion The cytotoxicity of both materials decreased over time. Zirconomer showed higher cytotoxicity than CGI at all time points.